Chronic Intermittent Hypoxia and Acetaminophen Induce Synergistic Liver Injury - Savransky, Vladimir (2008)
Obstructive sleep apnea (OSA) leads to chronic intermittent hypoxia (CIH) during sleep. OSA has been associated with liver injury. Acetaminophen (APAP) is one of the most commonly used drugs, which has known hepatotoxicity. The goal of the present study was to examine whether CIH increases liver injury, hepatic oxidative stress and inflammation induced by chronic APAP treatment. C57BL/6J mice were exposed to CIH or intermittent air (IA) for 4 weeks. Mice in both groups were treated with intraperitoneal injections of either APAP (200 mg/kg) or normal saline daily. A combination of CIH and APAP caused liver injury with marked increases in serum alanine aminotransferase, aspartate aminotransferase (AST), gamma glutamyl transferase and total bilirubin levels, whereas CIH alone induced only elevation in serum AST levels. APAP alone did not affect serum levels of liver enzymes. Histopathology revealed hepatic necrosis and increased apoptosis in mice exposed to CIH and APAP, whereas the liver remained intact in all other groups. Mice exposed to CIH and APAP exhibited decreased hepatic glutathione in conjunction with a five-fold increase in nitrotyrosine levels, suggesting formation of toxic peroxynitrite in hepatocytes. APAP or CIH alone had no effect on either glutathione or nitrotyrosine. A combination of CIH and APAP caused marked increases in pro-inflammatory chemokines, monocyte chemoattractant protein-1 and macrophage inflammatory protein-2, which were not observed in mice exposed to CIH or APAP alone. We conclude that CIH and chronic APAP treatment lead to synergistic liver injury, which may have clinical implications for patients with OSA.